2015
DOI: 10.1016/j.lindif.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The specific relation of visual attention span with reading and spelling in Dutch

Abstract: Visual attention span, the number of orthographic units that can be processed at a glance, has been shown to predict reading performance in orthographically opaque languages (i.e., French and English), independent from phonological awareness. Whether this relation is also found in Dutch, a more transparent orthography, was examined in two studies. Two unresolved issues are addressed. First, whether the contribution of visual attention span to reading was independent of rapid naming. Participants were 117 secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 49 publications
11
54
0
1
Order By: Relevance
“…The accuracy level at each of the five letter positions (from left to right) was almost at ceiling for the first two letters (showing that children were fine with reporting letters in itself) and then dropped. This pattern is very similar to that reported in previous studies using the global report version of the VAS task, showing that individual differences in VAS performance are mostly determined by differences in accuracy in letter positions three to five (Valdois et al, 2003;van den Boer, van Bergen, & de Jong, 2015).…”
Section: Resultssupporting
confidence: 90%
“…The accuracy level at each of the five letter positions (from left to right) was almost at ceiling for the first two letters (showing that children were fine with reporting letters in itself) and then dropped. This pattern is very similar to that reported in previous studies using the global report version of the VAS task, showing that individual differences in VAS performance are mostly determined by differences in accuracy in letter positions three to five (Valdois et al, 2003;van den Boer, van Bergen, & de Jong, 2015).…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the results indicate that there is a degree of multi-letter processing in the RAN that can be enhanced under certain conditions (in this case the insertion of lexical units). This supports previous studies suggesting that there is an aspect of multi-element processing in RAN (Bowers, 1995;Logan et al, 2011;Logan & Schatschneider, 2014;Protopapas et al, 2013), and could explain the previously reported correlations between VAS and RAN performance (van den Boer et al, 2014(van den Boer et al, , 2015.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, lexical access from the words' identification should interfere with letter-by-letter naming, thus increasing overall naming speed. Lastly, RAN and VAS skills are expected to correlate positively within both bilingual groups (van den Boer et al, 2014(van den Boer et al, , 2015.…”
mentioning
confidence: 99%
“…A second limitation is that, although we included the two‐core elements phoneme deletion and spoonerism to represent phonological awareness, we only had one measure of verbal working memory. In future research, visual working memory may also be included, because it links to different elements in the reading process than verbal working memory (van den Boer, van Bergen, & de Jong, 2015). Measuring different aspects of working memory will help to understand which aspect of working memory is restricted to phonological awareness and word reading efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In future research, visual working memory may also be included, because it links to different elements in the reading process than verbal working memory (van den Boer, van Bergen, & de Jong, 2015). Measuring different aspects of working memory will help to understand which aspect of working memory is restricted to phonological awareness and word reading efficiency.…”
Section: Discussionmentioning
confidence: 99%